Dissenting Approaches of Islamic Economics: The Contemporary Juristic Discussion of Riba - Fuady Abdullah; Moh. Mukhlas (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
Along with the rapid growth and spread of Islamic economic enterprises, some of their products have prompted debates among Islamic scholars about their permissibility and whether they comprise usury (riba). Even though riba is one of the central concepts in Islamic economics, the ruling of riba and its definition is still among those objects of the ongoing long debates and discussions among Islamic scholars and economists. This issue comes about from a broader question about which Islamic economic system should be developed as an alternative to its conventional counterpart. By examining discussions on riba found in contemporary literature, it can be seen that the question is discussed through different approaches. At the same time, these approaches are used to understand and implement Sharia juristic principles in the economy. There are three approaches; the modernist approach, the revivalist approach, and the literalist approach. To further understand these approaches, this paper identifies some main topics of the ongoing debate among the proponents of these approaches, namely, the position of Fiqh opinions in defining Islamic economic concepts, the objectives of Sharia to comply in economic activities, and also the question of the applicability of concepts concluded by each approach.